Uma proposta pedagógica para uso de modelagem matemática com suporte na Sequência Fedathi no contexto de uma EEMTI do estado do Ceará - Mendonça, Adriana Ferreira (2024)
The teaching of Mathematics through the teaching trend of Mathematical Modeling, although it presents satisfactory results in various research, presents many impasses in its implementation. It is common to identify several obstacles in its implementation. In this sense, the objective of this thesis was to develop a pedagogical proposal for the use of Mathematical Modeling to implement activities in the classroom, associated with the Fedathi Sequence to strengthen teaching praxis, in a Full-Time School – EEMTI – in the state from Ceará. Aspects that contribute to the non-implementation of this methodology by teachers are considered relevant – such as compliance with the curriculum, teaching time – which constitute points of tension in the preparation and application of these activities. The relevance of the research lies in understanding the phenomenon of low adherence among teachers when using this methodology, which constitutes an innovation for the literature that deals with teaching and learning methods, in addition to expanding the field of understanding of Mathematical Modeling from an educational training perspective. Specifically, we seek to: (1) Analyze the context of EEMTI to structure the pedagogical proposal for Mathematical Modeling and Fedathi Sequence activities; (2) Develop the planning and application of Mathematical Modeling activities with teachers focusing on the specificities of EEMTI; (3) Describe the pedagogical proposal for the use of Mathematical Modeling activities, supported by the Fedathi Sequence, in an EEMTI in the state of Ceará. Methodologically, the research will be qualitative in nature, characterized by the scope of the case study and divided into three stages associated with each of the specific objectives. The research results showed that the EEMTI context is favorable to the development of Modeling activities supported by the Fedathi Sequence and that teaching participation in the preparation of the proposal was essential. Additionally, the results in the preparation of the Reference Planning for the application of Mathematical Modeling activities, the foundations of the Fedathi Sequence, steps, and principles, were fundamental for the proposal to offer EEMTI broad and quality support.